The management of the director and teachers’ feedback, in a public university of Peru (LACCEI, 2024)
The objective of the study was to establish strategies to strengthen the management of the directors of the Faculty of Social Sciences and Humanities, Enrique Guzmán y Valle National University of Education, through feedback to teachers in times of pandemic. From the data obtained, three solution strategies were proposed: Raise awareness among the management staff in giving feedback to the teacher in the pedagogical actions Train managers and provide technical assistance, accompany, and monitor teachers. Finally, it is concluded that the quality of teaching-learning will improve due to the feedback of managers towards teachers. Keywords: satisfaction users training awareness monitoring.